Mechanism, follow-up and recurrence of inappropriate therapy in the PRAETORIAN trial: action reduces recurrence. (19th May 2022) - Pepplinkhuizen, S; Delnoy, PPHM; Olde Nordkamp, LRA; Kuschyk, J; Bonnemeier, H; Bijsterveld, NR; Boersma, LVA; El-Chami, MF; Smeding, L; Van Der Stuijt, W; De Weger, A; Richter, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Boston Scientific Corporation Background: The PRAETORIAN trial demonstrated that the subcutaneous ICD (S-ICD) is non-inferior to the transvenous ICD (TV-ICD) with regard to inappropriate shocks (IAS) and complications. Inappropriate therapy is an undesirable side effect of ICD therapy. Purpose: This pre-specified secondary analysis evaluates all inappropriate therapy in the PRAETORIAN trial and subsequent action to reduce recurrence of IAS. Methods: The PRAETORIAN trial is an international, multicentre, randomised trial, which included patients with an indication for ICD therapy. In total, 849 patients were randomised to receive an S-ICD (N=426) or TV-ICD (N=423). ICD programming was mandated by protocol. Inappropriate therapy was defined as any ICD therapy on a different rhythm than ventricular tachycardia or ventricular fibrillation. A day with inappropriate therapy was defined as all device episodes on the same day. Mechanism, actions and recurrence rate were determined using days with inappropriate therapy. Results: In the S-ICD group, 42/426 (10%) patients received inappropriate therapy, compared to 42/423 (10%) patients in the TV-ICD group (P=0.97). In total, 41 patients in the S-ICD and 29 patients in the TV-ICD group received at least one IAS (P=0.14). The total number of IAS in the S-ICD and TV-ICD group is comparable (124 vs. 130, P=0.88). The most common underlying mechanism of inappropriate therapy was T-wave oversensing in the S-ICD group (45%) and a supraventricular tachycardia (SVT) in a therapy zone in the TV-ICD group (93%). When no action was undertaken after the first IAS, the recurrence rate of an IAS of the same etiology was 56% (5/9) in the S-ICD group and 50% (4/8) in the TV-ICD group. An action, such as a change in medication, a change in programming, an invasive action or lifestyle advise resulted in a recurrence rate of 23% (7/30) in the S-ICD group and 30% (6/20) in the TV-ICD group. The recurrence rate was significantly higher when no action was undertaken versus any action (P=0.04) (Figure 1.). A change in programming resulted in a lower recurrence rate than a change in medication (S-ICD, 40% vs. 27% and TV-ICD, 44% vs. 17%). After an invasive action no recurrence of IAS occurred in both groups. Invasive actions were more common in the S-ICD group (7/41, vs. 1/29). In the S-ICD group the most common action was a change in programming (17/41), mainly when the underlying mechanism of IAS was cardiac oversensing. In the TV-ICD group the most common action was a change in medication (12/29), mainly and only when the underlying mechanism of IAS was an SVT (Figure 2.). Conclusion: The total number of IAS and total patients receiving IAS are not statistically different between the S-ICD group and the TV-ICD group. However, the underlying mechanism and action after IAS differ and are associated with the different sensing of the ICDs. The recurrence rate after a first IAS was significantly higher when no action was undertaken.